THERAPEUTIC AND PREVENTIVE MEASURES FOR PERIODONTAL DISEASES IN PREGNANT WOMEN - Sodiqova Shoira Amriddinovna; Shirmonxo’jayev Javoxirxo’ja; Shokirov Baxtiyor; Rabbimov Jasur; Usmonov Shaxriyor (Web of Journals Publishing, 2024)
Pregnancy is a transformative period in a woman's life, marked by physiological changes that extend beyond the obvious physical manifestations. One aspect that often goes unnoticed is the impact of pregnancy on oral health, specifically the increased susceptibility to periodontal diseases. Periodontal diseases, including gingivitis and periodontitis, can pose risks not only to the mother's oral health but also to the overall well-being of both the mother and the developing fetus. This article explores the therapeutic and preventive measures crucial for managing periodontal diseases in pregnant women.
Keywords: pregnancy, oral health, gingivitis, periodontitis, preventive measures, therapeutic interventions, dental check-ups, oral hygiene, hormonal changes.